The Intercultural Values and Social Connectedness of International Female Doctoral Students in Australia - Syed, Sabrina (Journal of Interdisciplinary Studies in Education, 2023)
This paper explored the multiple layers of social and intercultural adjustment challenges experienced by international female doctoral students in Australia. The paper investigates multiple dimensions of sociocultural differences between the students’ native and host countries, including sociocultural context, community engagement, personal and social lives, and the intersection of more commonly researched sociocultural identities. This investigation is undertaken within the epistemological positioning of feminist standpoint theory and intersectionality. In addition, a narrative inquiry approach and a thematic analysis are used to understand the students’ social lives and issues of adjustment to a new culture. Themes like intercultural understanding, social connectedness and adjustment issues are used to encapsulate the students’ views about their social positionality and understanding of their lives during PhD in Australia.